Vitamin D in food samples based on a TDS approach - Ravasco, Francisco (2020)
Vitamin D occurs in two distinct forms: vitamin D2 (ergocalciferol) and vitamin D3 (cholecalciferol). It is necessary in human diet to calcium absorption and regulation, as well as bone development and in the immune system. Humans naturally produce vitamin D through exposure to sunlight. Vitamin D deficiency became a major health concern in many societies, as ever-growing numbers of people began spending most of their daily routines indoors and removed from sunlight. According EFSA, the daily intake values should be between 10 μg/day for infants and 15 μg/day for adults, for both genders. Objectives: To evaluate the vitamin D content of representative samples of the Portuguese consumption, based on a Total Diet Study (TDS).